Characterization of HMGA1P6 transgenic mouse embryonic fibroblasts. Issue 18 (16th September 2020) - De Martino, Marco; Palma, Giuseppe; Arra, Claudio; Chieffi, Paolo; Fusco, Alfredo; Esposito, Francesco
ABSTRACT: Latest studies have shown that deregulated pseudogene transcripts contribute to cancer working as competing endogenous RNAs. Our research group has recently demonstrated that the overexpression of two HMGA1 pseudogenes, HMGA1P6 and HMGA1P7, has a critical role in cancer progression. These pseudogenes work sustaining the expression of HMGA1 and other cancer-related genes. We generated a mouse model overexpressing HMGA1P6 to better study the HMGA1 -pseudogene function in a more physiological context. Here, we show the proliferation rate and the susceptibility to senescence of mouse embryonic fibroblasts obtained from HMGA1P6 -overexpressing mice to better characterize the HMGA1-pseudogene function. Indeed, our study reports that mouse embryonic fibroblasts (MEFs) derived from HMGA1P6 mice express higher HMGA1 mRNA and protein levels. Moreover, these cells grow faster and senesce later than wild-type sustaining the oncogenic role of ceRNA crosstalk mediated by HMGA1Ps .